The Influence of Human Resource Quality and Information Technology Use on Employee Performance in The Timeliness of The Final Draft of The RPJMD of Bitung City - Sambur, Isser Harell; Bogar, Wilson; Sendouw, Recky H E (International Journal of Information Technology and Education, 2024)
This study aims to (1) Identify the Influence of Human Resource Quality on Employee Performance in the Timeliness of the Final Draft of the Bitung City RPJMD, (2) Identify the Influence of Information Technology Utilization on Employee Performance in the Timeliness of the Final Draft of the Bitung City RPJMD. (3) Analyze the Joint Influence of Human Resource Quality and Information Technology Utilization on Employee Performance in the Timeliness of the Final Draft of the Bitung City RPJMD. This study was conducted using a quantitative approach. Quantitative research methods are used to research certain populations or samples, data collection using research instruments, and data analysis is quantitative or statistical to test the established hypothesis. The results of the study indicate that overall, Human Resource Quality and Information Technology Utilization together provide an effective contribution of 48.62% to the Timeliness of the Final Draft of the Bitung City RPJMD. This means that these two variables significantly affect the Accuracy and Timeliness of the Final Draft of the Bitung City RPJMD. There are 51.38% of the Accuracy in Timeliness of the Final Draft of the Bitung City RPJMD that are influenced by other variables not discussed in this study, indicating that there are additional factors that also need to be considered to improve the Accuracy in Timeliness of the Final Draft of the Bitung City RPJMD as a whole.